ANTIVIRAL TREATMENT IN PATIENTS WITH INFLUENZA INFECTION: A SYSTEMATIC REVIEW - Andhira Prilialoka, Dhea (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Influenza is a viral infection which is characterized by fever, cough, and runny nose. Influenza may cause a disease in varying degrees, mild to severe. Influenza is a self-limiting disease, however, patients with comorbidities may experience severe sequelae. Due to this, antiviral agents are very crucial for influenza patients.Objective: This article aims to discuss treatment agents for influenza patients.Methods: This manuscript was prepared based on Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. PRISMA is the basis of determining the criteria used in conducting this systematic review. The desired result is a patency comparison between the two techniques. The articles included should be published between 2013 until 2023. The keywords used in search strategy were "antiviral" and "influenza".Results: The results were presented in Table 1. 267 articles from PubMedn and 212 articles from SagePub were obtained from initial search. The final screening process resulted in 10 publications.Conclusion: Research showed that baloxavir was more effective than NAI, while NAI was more effective than placebo. Baloxavir had more severe side effects compared to NAI, though both drugs were safe for children.